Research Hotspots and Trends in Workplace Violence Among Healthcare Professionals: A Bibliometric and Visualization Analysis Based on Web of Science - Lin Q; Liu L; Fu M; Chen K; Li L; Jiang M; Wu J (Journal of Multidisciplinary Healthcare)
Qin Lin,1,2,* Linfeng Liu,3,* Mengxue Fu,2,* Kanlun Chen,4,* Ling Li,1 Minmin Jiang,1 Jijun Wu5 1Shulan International Medical College, Zhejiang Shuren University, Hangzhou, Zhejiang, People’s Republic of China; 2College of Nursing and Allied Health Sciences, St. Paul University Manila, Manila, Metro Manila, Republic of the Philippines; 3Department of Discipline Research, Sichuan Nursing Vocational College, Chengdu, Sichuan, People’s Republic of China; 4Department of Hospital Administration, the First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China; 5Department of Cardiology, People’s Hospital of Deyang, Deyang, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Minmin Jiang, Email pingwan999@yeah.net Jijun Wu, Email tianmin6560@163.comBackground: Workplace violence is a significant issue in healthcare settings, affecting the physical and psychological health of healthcare professionals and compromising patient care quality. Despite growing concerns, a comprehensive understanding of the research landscape remains limited.Objective: This study aims to analyze the research hotspots and trends in workplace violence among healthcare professionals through bibliometric and visualization analysis, providing insights into the current state of research and identifying future directions.Methods: We conducted a comprehensive search of the Web of Science database from inception to August 10, 2024, identifying relevant studies on workplace violence among healthcare professionals. A total of 937 publications were included for analysis. Bibliometric and visualization analysis software (CiteSpace, VOSviewer, BICOMB, and gCLUTO) were used to analyze authors, affiliations, and keywords, and to visualize research trends and hotspots.Results: Our analysis revealed 9 distinct clusters of research hotspots, including risk factors, affected departments, demographics, and impacts of workplace violence. Key findings indicate that emergency departments and nursing staff are particularly vulnerable, with significant impacts on mental health and job satisfaction. The study also highlights the increasing trend of publications over the years, reflecting growing research interest in this area.Conclusion: The findings reveal that workplace violence is a significant issue affecting the mental and physical health of healthcare professionals, with notable impacts on job satisfaction, patient care quality, and overall organizational climate. Future efforts should focus on strengthening collaborations and developing targeted interventions to mitigate workplace violence, thereby enhancing the safety and quality of healthcare services.Keywords: healthcare professionals, workplace violence, research hotspots, bibliometric analysis, visualization analysis